Targeting the mitochondrial pyruvate carrier attenuates fibrosis in a mouse model of nonalcoholic steatohepatitis. Issue 5 (30th March 2017) - McCommis, Kyle S.; Hodges, Wesley T.; Brunt, Elizabeth M.; Nalbantoglu, Ilke; McDonald, William G.; Holley, Christopher; Fujiwara, Hideji; Schaffer, Jean E.; Colca, Jerry R.; Finck, Brian N.
Abstract : Diseases of the liver related to metabolic syndrome have emerged as the most common and undertreated hepatic ailments. The cause of nonalcoholic fatty liver disease is the aberrant accumulation of lipid in hepatocytes, though the mechanisms whereby this leads to hepatocyte dysfunction, death, and hepatic fibrosis are still unclear. Insulin‐sensitizing thiazolidinediones have shown efficacy in treating nonalcoholic steatohepatitis (NASH), but their widespread use is constrained by dose‐limiting side effects thought to be due to activation of the peroxisome proliferator–activated receptor γ. We sought to determine whether a next‐generation thiazolidinedione with markedly diminished ability to activate peroxisome proliferator–activated receptor γ (MSDC‐0602) would retain its efficacy for treating NASH in a rodent model. We also determined whether some or all of these beneficial effects would be mediated through an inhibitory interaction with the mitochondrial pyruvate carrier 2 (MPC2), which was recently identified as a mitochondrial binding site for thiazolidinediones, including MSDC‐0602. We found that MSDC‐0602 prevented and reversed liver fibrosis and suppressed expression of markers of stellate cell activation in livers of mice fed a diet rich in trans‐fatty acids, fructose, and cholesterol. Moreover, mice with liver‐specific deletion of MPC2 were protected from development of NASH on this diet. Finally, MSDC‐0602 directly reduced hepatic stellate cell activation in vitro, and MSDC‐0602 treatment or hepatocyte MPC2 deletion also limited stellate cell activation indirectly by affecting secretion of exosomes from hepatocytes. Conclusion : Collectively, these data demonstrate the effectiveness of MSDC‐0602 for attenuating NASH in a rodent model and suggest that targeting hepatic MPC2 may be an effective strategy for pharmacologic development. (Hepatology 2017;65:1543‐1556).